Four new species of orchids (Orchidaceae) in eastern Vietnam - Averyanov, Leonid V.; Duy, Nong Van; Vinh, Tran Thai; Hoi, Quach Van; Cong, Vu Kim (Phytotaxa, 2015)
Dendrobium thinhii (D. sect. Breviflores), Sarcoglyphis tichii, Taeniophyllum phitamii (T. subgen. Codonosepalum Schltr.) and Trichoglottis canhii are described and illustrated as species new to science. All are local endemics of the area associated with Truong Son Range (Annamese Cordilleras) within territories of Dac Lak, Kon Tum and Lam Dong provinces of the southern Vietnam known in national geography as the Central Highlands or Tay Nguyen Plateau. All discovered plants are well-defined, taxonomically isolated species representing very strict plant endemism quite typical for the southern part of eastern Indochina.